Recreating a 15th-century chamber: digital humanities and research into the past - Caballero Escamilla, Sonia; Valdivia García, Miguel (De Medio Aevo, 2026)
The advantages that 3D technologies provide for the reconstruction of lost heritage and the need to transfer scientific knowledge to society have led us to propose the virtual reconstruction of a 15th-century chamber within the framework of the National Plan research project "Things by Their Name: (Re)building the House with Words and Images, 15th and 16th Centuries" (2023-2027). Our objective is to focus on the architectural space, as well as the furnishings and furnishings, while also allowing for a glimpse of the emotional aspect. Our aim is not to recreate a specific location, but rather to visualize the general appearance that a chamber in a Castilian noble home from the late 15th to early 16th centuries might have had. We have chosen to select aspects that are common throughout the region, such as the confluence of the Nordic aesthetic model, in the Flemish style, with the Andalusian aesthetic, the presence of beds with walls, textiles, chests, toiletries, ceramics, amulets, as well as furniture, images, and objects intended for devotional practices.